2022
DOI: 10.1093/geront/gnac028
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Research on Older People and Intergenerational Relations in the Context of Climate Change

Abstract: Background and Objectives In view of the inherited temporal dimension of climate change, this study aims to highlight diverse intergenerational effects and coping strategies by examining the state of literature on older people and intergenerational relations in the context of climate change Research Design and Methods A scoping review of peer-reviewed scientific literature was conducted. We searched the following bibliographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 41 publications
0
43
1
Order By: Relevance
“…In addition to joining climate protests, older adult-led organizations like Climate Legacy, Elders Climate Action, Grandparents Climate Action, and the International Council of Grandmothers are fighting for a livable future for their children and grandchildren. Older people also can serve as the bearers of knowledge of traditional practices transmitted to the younger generations (Ayalon et al, 2022). Hence, we should strive to encourage solidarity between the generations, rather than division, in further mitigation efforts towards a healthy climate for healthy aging and healthy longevity (World Health Organization, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to joining climate protests, older adult-led organizations like Climate Legacy, Elders Climate Action, Grandparents Climate Action, and the International Council of Grandmothers are fighting for a livable future for their children and grandchildren. Older people also can serve as the bearers of knowledge of traditional practices transmitted to the younger generations (Ayalon et al, 2022). Hence, we should strive to encourage solidarity between the generations, rather than division, in further mitigation efforts towards a healthy climate for healthy aging and healthy longevity (World Health Organization, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The review concluded that both younger and older people are affected by age-based discrimination related to climate change as well as by direct and indirect climate change effects including mitigation and adaptation efforts. Nonetheless, differences between the generations can be overcome by stressing the solidarity between the generations and the valued knowledge of older people who can contribute to climate change mitigation and adaptation efforts (Ayalon et al, 2022).…”
Section: Climate Change Intergenerational Tension and Ageismmentioning
confidence: 99%
See 3 more Smart Citations